Pendampingan waste management Koperasi Melati Jaya dalam mendukung kota berkelanjutan - Hadi Prayitno; Rahayu Lestari; Dini Hardilla; Angelia Eka Salsabillah; Deno Ratu Alam; Rizal Khairudin; Hesti Hesti (Yumary: Jurnal Pengabdian kepada Masyarakat, 2021)
Purpose: This study aimed to increase the knowledge and ability of Koperasi Melati Jaya's waste management. Waste management capabilities can reduce the volume of waste to the landfill. Method: The program began the dissemination of commitment to waste management to contribute to SDGs achievement, assistance in manufacturing verticulture, hydroponics, eco-bricks, garden architects, and utilizing waste. Evaluation was carried out to improve the waste management program. Results: Through this program, more than 70% of the cooperative's members manage waste using the 7R principle. Knowledge, attitudes, and abilities in recycling waste into hydroponics, verticulture, and eco-bricks have increased. The conversion of waste into valuable products indirectly contributes to reducing the volume of waste from TPA Bakung. The income of cooperative members and the fact that fresh vegetables in the city of Bandar Lampung have increased. Conclusions: The consistency program can bring Sukamenanti Baru close to zero waste so that it becomes a livable village. Indirectly, it supports the achievement of SDGs in Bandar Lampung City. Keywords: Garbage, Women, Cooperatives, SDGs